Clinical management of metformin overdose: A case report - KARSLI, SEHER; YURDUN, TÜRKAN (Ondokuz Mayis Universitesi, 2017)
Metformin is first-line therapy in diabetes mellitus treatment. Metformin intoxication may cause lactic acidosis. A 29-year-old woman presented to our emergency department with loss of consciousness. Arterial blood gas revealed severely increased anion gap lactic acidosis. Continuous venovenous hemofiltration was performed for 39 h. After extracorporeal treatment, the acidosis resolved and the patient became conscious. There is no specific treatment for metformin intoxication; current treatment is supportive only. Our aim is to highlight the diagnosis, chromatographic measurement of the drug blood level, and management of metformin overdose. © 2017 OMU.
Keywords: Hemofiltration; Hypoglycemia; Lactic acidosis; Metformin; Overdose